Afghanistan post-2014: implications for the stability of Russia’s southern periphery (Comillas Journal of International Relations, 2015)
Afghanistan and the wider Central Asian region constitute part of Russia’s “southern underbelly”, a term that underscores the sense of vulnerability it feels along its southern border. Russia’s security concerns in the region focus on cross-border instability, including the spread of religious extremism and drug trafficking. Moscow is apprehensive about the possibility of a further deterioration in Afghanistan’s internal situation after the withdrawal of international forces in 2014, and has consequently been taking steps to bolster the security of both Afghanistan and its Central Asian neighbours through a variety of means. This paper analyses the drivers of Russian policy and assesses its perceptions of threat and security in the region, focusing particularly on the implications for Russia of the 2014 drawdown of the international stabilisation operation in Afghanistan (ISAF).
Keywords: Russia; Central Asia; ISAF; transnational security challenges; military assistance; Collective Security Treaty Organisation (CSTO)